Can a simple test of functional capacity add to the clinical assessment of diabetes?. Issue 8 (29th December 2015) - Stewart, T.; Caffrey, D. G.; Gilman, R. H.; Mathai, S. C.; Lerner, A.; Hernandez, A.; Pinto, M. E.; Huaylinos, Y.; Cabrera, L.; Wise, R. A.; Miranda, J. J.; Checkley, W.
Abstract: Aim: To identify impairment in functional capacity associated with complicated and non‐complicated diabetes using the 6‐min walk distance test. Methods: We enrolled 111 adults, aged ≥40 years, with Type 2 diabetes from a hospital facility and 150 healthy control subjects of similar age and sex from a community site in Lima, Peru. All participants completed a 6‐min walk test. Results: The mean age of the 261 participants was 58.3 years, and 43.3% were male. Among those with diabetes, 67 (60%) had non‐complicated diabetes and 44 (40%) had complications such as peripheral neuropathy, retinopathy or nephropathy. The mean unadjusted 6‐min walk distances were 376 m and 394 m in adults with and without diabetes complications, respectively, vs 469 m in control subjects ( P <0.001). In multivariable regression, the subjects with diabetes complications walked 84 m less far (95% CI ‐104 to ‐63 m) and those without complications walked 60 m less far (‐77 to ‐42 m) than did control subjects. When using HbA1c level as a covariate in multivariable regression, participants walked 13 m less far (‐16.9 to ‐9.9 m) for each % increase in HbA1c . Conclusions: The subjects with diabetes had lower functional capacity compared with healthy control subjects with similar characteristics. Differences in 6‐min walk distance were even apparent in the subjects without diabetes complications. Potential mechanisms that could explain this finding are early cardiovascular disease or deconditioning. What's new?: In this study we identified impairment in functional capacity among adults with complicated and non‐complicated diabetes using the 6‐min walk test. We sought to show the potential clinical use of the 6‐min walk test in the assessment and care of adults with Type 2 diabetes mellitus. We found a statistically significant difference in 6‐min walk distance between healthy adults and adults with and without complicated diabetes.